The complexity of polarization in social dynamics - Carpio Rivas, David Mateo (2023)
The rise of extreme polarization of opinions in societies is a problem of much interest that has recently been approached in the context of complex systems. In this work, we investigate the dynamics of opinion formation using agent-based models to understand the processes underlying polarization in social networks. To study the dynamics of interactions between agents, we employ the Attraction-Repulsion Agent-Based Model that leads to polarization recently proposed by R. Axelrod and his collaborators. We introduce two different mechanisms for controlling and preventing extreme polarization in this model. First, we study the influence of mass media, considered as an external global field, on opinion formation dynamics. Secondly, we consider an extension of the Attraction-Repulsion Model as a coevolutionary network dynamics, where both the opinions of the agents and their mutual connections vary over time. Our results reveal that, in a social system capable of extreme polarization, mass media messages located around the middle of the opinion spectrum can slow down and even prevent the polarization process. In contrast, extremist messages push agents’ opinions toward the opposite extreme, leading to asymmetric polarization within the system. For the coevolutionary model, we found that the rewiring of connections based on the principle of homophily can lead to the emergence of a central-opinion group, thus avoiding polarization in a low-tolerant network.